Computer-Human Interaction 8th Asia-Pacific Conference, APCHI 2008 Seoul, Korea, July 6-9, 2008, Proceedings - Lee, Seongil; Choo, Hyunseung; Ha, Sungdo; Shin, In Chul (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2008)
This book constitutes the refereed proceedings of the 8th Asia Pacific Conference on Computer Human Interaction, APCHI 2008, held in Seoul, Korea, in July 2008. The 45 revised full papers presented together with 6 invited papers were carefully reviewed and selected from 151 submissions. The topics addressed span the entire spectrum of HCI, including ubiquitous computing, groupware, intelligent system design, human-robot interaction, virtual / augmented environment, vision-based system, mobile interaction design, novel interaction technique, usability, Web accessibility, and elderly.